SGLT2: new approaches to combination therapy of type 2 diabetes mellitus - I. V. Kononenko; O. M. Smirnova (Медицинский совет, 2016)
Despite the emergence of new antidiabetic drugs, diabetes type 2 treatment remains a relevant issue. In order to standardize and optimize medical care to patients with diabetes, global and national algorithms for type 2 diabetes treatment were developed. [1, 2] The current algorithms focus on an individual approach, safety and effectiveness of treatment. A balance should be maintained between achieving optimal glycemic control and safety of therapy.